2019
DOI: 10.1029/2019jd030257
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a 1998 Observing System Change on MERRA‐2‐Based Ozone Profile Simulations

Abstract: Model simulations of ozone (O3) driven by meteorological reanalyses are useful for filling observational gaps and interpreting observed O3 variability and trends. However, the transport circulation of reanalysis products is impacted by changes to the observing system (the data assimilated into the reanalyses). We examine the impacts of these changes on simulated O3 from two models, Global Modeling Initiative (GMI) Chemistry Transport Model (GMI CTM) and Modern‐Era Retrospective Analysis for Research Applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

6
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 39 publications
4
28
2
Order By: Relevance
“…The negative ozone anomalies during the period of 1992-1996 are consistent with the chemical and dynamical perturbations following the 15 June 1991 eruption of Mt. Pinatubo (Hadjinicolaou et al, 1997;Stenchikov et al, 2002;Rozanov et al, 2002). The negative ozone anomaly in 2015-2016 is associated with stratospheric circulation changes caused by the unusually warm ENSO event coinciding with a disrupted quasi-biennial oscillation (QBO) during that period (Tweedy et al, 2017;Diallo et al, 2018).…”
Section: Winter and Spring Ozone Iav In The Lower Stratosphere And Trsupporting
confidence: 62%
“…The negative ozone anomalies during the period of 1992-1996 are consistent with the chemical and dynamical perturbations following the 15 June 1991 eruption of Mt. Pinatubo (Hadjinicolaou et al, 1997;Stenchikov et al, 2002;Rozanov et al, 2002). The negative ozone anomaly in 2015-2016 is associated with stratospheric circulation changes caused by the unusually warm ENSO event coinciding with a disrupted quasi-biennial oscillation (QBO) during that period (Tweedy et al, 2017;Diallo et al, 2018).…”
Section: Winter and Spring Ozone Iav In The Lower Stratosphere And Trsupporting
confidence: 62%
“…We cannot expect agreement with observations for a climate simulation to be better, and thus both O3v1 and O3v2 can be considered a match. The large pre-OMI to post-OMI shift in UCI SDs may be caused by the ECMWF data assimilation shift in satellite systems (Wargan et al, 2017), as this has been documented for the MERRA-2 meteorological fields (Douglass et al, 2017;Stauffer et al, 2019). We present a Taylor diagram for the mean annual SCO cycle [1] and the SD/SCO [2] in Fig.…”
Section: Stratospheric Column Ozonementioning
confidence: 99%
“…Models have likewise been relied upon to derive tropospheric OH abundance and its evolution. Stevenson et al (2006) found a large spread in τ CH 4 (6.3 to 12.5 years) from a suite of atmospheric chemistry models in an analysis performed more than a decade ago. A total of 7 years later, the Atmospheric Chemistry and Climate Model Intercomparison Project (ACCMIP) generated both historical (Naik et al, 2013) and future (Voulgarakis et al, 2013) simulations from numerous chemistry-climate models, revealing still large discrepancies not only in present-day τ CH 4 (with values ranging from 7.1 to 14.0 years) but also in how τ CH 4 is expected to vary through the year 2100 given common emissions scenarios.…”
Section: Introductionmentioning
confidence: 97%